Regulation of the Cell Cycle, Apoptosis, and Proline Accumulation Plays an Important Role in the Stress Response of the Eastern Oyster Crassostrea Virginica - Li, Cui; Wang, Haiyan; Guo, Ximing (Frontiers in Marine Science, 2022)
Background: Understanding how organisms respond and adapt to environmental changes is central to evolutionary biology. As a sessile organism that has adapted to life in estuaries and intertidal zones, the eastern oyster Crassostrea virginica can tolerate wide fluctuations in temperature and salinity and survive for weeks out of water. To understand the molecular mechanisms underlying the remarkable stress tolerance of the eastern oyster, we studied the transcriptomic changes induced by exposure to air and cold stress. Eastern oysters were maintained for 7 days under four conditions, namely, in seawater (normal) at 22°C, in air at 22°C, in seawater at 5°C and in air at 5°C, and then sampled for RNA sequencing. Results: The transcriptomic analysis revealed that many genes involved in cell cycle progression and DNA replication were downregulated in oysters exposed to air and cold, which indicated that stress inhibits cell division. Exposure to air at 22°C induced a concerted inhibition of apoptosis through the upregulation of expanded inhibitors of apoptosis and the downregulation of caspases. Interactions between TNF and NF-κB signalling indicated a reductions in the inflammatory response and immune functions. Key genes for proline production, fatty acid synthesis and chromosomal proteins were upregulated during exposure to low temperatures, which suggested that proline accumulation, energy conservation, and epigenetic modification of chromosomes are important for coping with cold stress. The upregulation of melatonin, FMRFamide, and neural acetylcholine receptors indicate the significance of the neurohormonal regulation of homeostasis. Conclusion: These results show that the regulation of cell division, apoptosis, proline accumulation, neurohormonal signalling, and epigenetic modifications plays an important role in the stress response of the eastern oyster and thus provide insights into the molecular bases of the stress response and adaptation.